Effectiveness of Educational and Behavioral Models in the Reduction of Inappropriate Antibiotic Prescribing in United States Health Delivery Settings - R. Viel, Carl; Martin, Pilar (International Journal of Innovative Research in Medical Science, 2017)
Inappropriate antibiotic prescribing represents the most avoidable cause of resistance to antimicrobial drugs (CDC, 2015). As prevention constitutes the core principles of public health, any intervention addressing inappropriate antibiotic prescribing is susceptible of improving the health outcomes of communities as well as reducing the risk of resistance capable of inducing the worsening of the antimicrobial pandemic. Policymakers and public health leaders implemented several measures to tackle antibiotic resistance. Among those, we can mention educational training and behavioral interventions using either clinical decision support system, intrapersonal or interpersonal models to support changes in antibiotic prescribing. This project consisted of a systematic narrative review of seven studies describing interventions implemented to undertake the problem of inappropriate antibiotic prescribing in the United States (US). I focused on conducting a qualitative analysis of selected peer-reviewed papers. The purpose was to evaluate these different interventions and proceed to a comparative analysis that would permit us identifying the most efficient method to address this public health problem. Seven US experimental study designs evaluating educational and behavioral approaches were retained (Metlay 2016; Gonzales 2013; Gerber 2013; Meeker 2016; Mc Ginn 2015; Meeker 2014; Mainous 2013). All interventions from each selected study produced a distinct improvement in the reduction of inappropriate antibiotic rate for acute respiratory tract infections (ARTI). The decrease in antibiotic prescribing was considered the main favorable outcome described in the studies indicating a potential reduction in the risk of antibiotic resistance. Despite the encouraging findings from the systematic review, further investigations are needed to depict intervention that will be able to reduce inappropriate prescribing in hospitals and ambulatory health practices in the United States.